2017
DOI: 10.18632/aging.101216
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and the natural lifespan limit in humans

Abstract: An ongoing debate in demography has focused on whether the human lifespan has a maximal natural limit. Taking a mechanistic perspective, and knowing that short telomeres are associated with diminished longevity, we examined whether telomere length dynamics during adult life could set a maximal natural lifespan limit. We define leukocyte telomere length of 5 kb as the ‘telomeric brink’, which denotes a high risk of imminent death. We show that a subset of adults may reach the telomeric brink within the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 48 publications
4
91
1
1
Order By: Relevance
“…12,13,25 Incremental telomere shortening, while, quintessential to aging, the process is also crucial in cancer development. 12,13,25 Incremental telomere shortening, while, quintessential to aging, the process is also crucial in cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,25 Incremental telomere shortening, while, quintessential to aging, the process is also crucial in cancer development. 12,13,25 Incremental telomere shortening, while, quintessential to aging, the process is also crucial in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Constitutive telomere length, a polygenic trait with high estimated heritability, has hitherto been demonstrated to be associated with nine different genetic loci, with 6 harboring genes related to telomere homeostasis. 11,12 Telomere shortening is further influenced by oxidative damage and replicative stress caused by genetic, epigenetic, and environmental factors. 11,12 Telomere shortening is further influenced by oxidative damage and replicative stress caused by genetic, epigenetic, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their length, two types of telomeres at the end of chromosomes have been described (Delany et al, ): shorter or Class II telomeres (8–40 kb) and ultralong or Class III telomeres (up to 2.0 Mb). Class II telomeres are found to shorten with age in several species, such as humans, jackdaws and common terns (Bauch et al, ; Salomons et al, ; Steenstrup et al, ). Delany et al () found no evidence for shortening of Class III telomeres in chickens, but their analyses were cross‐sectional and data sets were small.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Wiener process first passage time to a boundary naturally captures the onset of HSC senescence when telomere length reaches the Hayflick limit (Hayflick and Moorhead 1961) as proposed by Dingli et al (2008). Furthermore, Steenstrup et al (2017) proposed telomere length plausibly establishes a biological limit to longevity. Accumulation of DNA mutations and epigenetic alterations should have similar properties in that once sufficient damage has accumulated DNA replication becomes unstable.…”
Section: Methodsmentioning
confidence: 96%